Penggunaan Indeks Vegetasi Berbasis Citra Multispektral Drone Untuk Deteksi Kondisi Pertumbuhan Padi Sawah - Iskandar, Wahyu; Muhammad, Almawardi; Munibah, Khursatul; Barus, Baba (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2025)
Monitoring on irrigated rice field is crucial to anticipate crop damage due to drought and flooding. However, conventional observation methods present complex challenges such as observer bias, point-based data, and limited observational coverage. Observations assisted by multispectral (MS) camera technology mounted on unmanned aerial vehicles (UAVs/drones) were able to address these issues but are still underdeveloped. This study reports the potential use of multispectral cameras mounted on a drone to assess the effects of drought and inundation on rice crops using vegetation indices such as the Normalized Difference Water Index (NDWI), Normalized Difference Vegetation Index (NDVI), and Normalized Difference Red-Edge Index (NDRE). Observations were conducted three times during the vegetative (10 days after transplanting), generative (45 days after transplanting), and ripening (80 days after transplanting) stages on Ciherang and IR64 rice varieties. The rice plants were subjected to different irrigation treatments: drying, flooding, and control. The results showed that the NDRE index had a poor response to vegetation during the vegetative stage but improved during the generative and maturation stages. Meanwhile, the growth of weeds among the rice plants affected the NDVI and NDWI values, especially under dry conditions, making these indices less reliable in such scenarios.